POROSITY VERSUS DEPTH CHARACTERISTICS OF SOME RESERVOIR SANDSTONES IN WESTERN INDONESIA - Bambang Widarsono (Scientific Contributions Oil and Gas, 2014)
Porosity is a petrophysical property that always draws attention due to its central role in determiningstorage capacity of hydrocarbon reservoirs. Accuracy for predicting porosity in reservoir affects much ofmany petroleum production related activities. Accordingly, various attempts have been devoted to study andmodel rock porosity including its relation with depth. In this study porosity data from as many as 4654 coresamples (1773 full-diameter core plugs and 2881 sidewall core samples) is used. The core samples were takenfrom 549 wells in 222 fi elds/structures located in eight producing sedimentary basins in western Indonesia.Main results of the study are facts that existing porosity-depth models derived from data obtained from otherregions are not usable for Indonesian cases, and therefore porosity-depth models are established for theeight sedimentary basins. It is hoped that these models can contribute signifi cantly to the understanding ofrock porosity trends with depth in western Indonesia.